Utilization of phase changing materials as air conditioning alternatives in eco-green systems - Hikma, Nurfi; Fitri, Ade; Izzah, Ramy Fitrah; Syahputra, Romi Fadli; Zulkarnain, Zulkarnain (Science, Technology and Communication Journal, 2022)
Prevention of global warming due to high energy consumption and greenhouse gases is a priority for local governments, especially in Pekanbaru City, Indonesia. The use of air conditioning has become a community habit of reducing the temperature of a hot room, but unexpected things can have a negative impact on the surrounding environment. Therefore, this paper provides a simple new idea by using a phase change material (PCM) in the form of an eco-green air cooler system (EGACY) application as a free and passive cooler. EGACY consists of salt hydrates, PCM boxes, iron pipes, fans, solar panels, and batteries as the main components and several other supporting components. The EGACY system works by absorbing cold air and stored by the PCM at night through pipes connected to the outside, then expelled during the day through indoor ceiling vents. The resulting temperature in the room can be controlled at a comfortable temperature from 25°C to 28°C. EGACY is believed to be able to provide the potential for environmentally friendly technology with renewable energy sources.